2004
DOI: 10.1302/0301-620x.86b3.14350
|View full text |Cite
|
Sign up to set email alerts
|

Complex fracture-dislocation of the proximal interphalangeal joint of the hand

Abstract: We reviewed 13 patients with a complex fracture-dislocation of the proximal interphalangeal joint of a finger and one patient with a complex fracture-dislocation of the interphalangeal joint of thumb. We had treated these injuries using a pins and rubbers traction system which had been modified to avoid friction of the pins against the bone during mobilisation of the joint in order to minimise the risk of osteolysis. A Michigan hand outcome questionnaire was used for subjective assessment. The active range of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
63
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(71 citation statements)
references
References 29 publications
(64 reference statements)
6
63
2
Order By: Relevance
“…The authors in several studies note that joint "remodeling" occurred, without defining this parameter. 23, 33 Syed et al found arthritis in only 1 of 9 cases, but noted that joint depression occurred in all remaining patients. 32 A strict definition was used in the current study to define arthritis and includes what other groups may have considered central depression or simply joint remodeling.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…The authors in several studies note that joint "remodeling" occurred, without defining this parameter. 23, 33 Syed et al found arthritis in only 1 of 9 cases, but noted that joint depression occurred in all remaining patients. 32 A strict definition was used in the current study to define arthritis and includes what other groups may have considered central depression or simply joint remodeling.…”
Section: Discussionmentioning
confidence: 97%
“…7-9 Unstable patterns require 16 static external fixation, 17 force-couple splints, 18 dynamic external fixation allowing passive ROM, 19 -22 and dynamic external fixation allowing both active and passive ROM. [23][24][25][26][27][28][29][30][31][32] Dynamic external fixators come in many varieties. All systems use pins or wires placed through the center of rotation of the proximal phalangeal head and through various sites in the middle phalanx that allow for motion of the PIP joint with the fixator in place.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Active/effective range of movement (arc) Complications Bain et al [ 15 ] ORIF or VPA and then monolateral ex-fi x 222 days 65.6° 1 septic arthritis 2 pin track infection Deshmukh et al [ 16 ] Fracture displacement ORIF 2 × residual subluxation Rutland et al [ 11 ] Dynamic ex fi x 16 months 89° 8 pin track infections Waris et al [ 10 ] Dorsal blocking wire 5 years 83° None reported Williams et al [ 24 ] Hemi-hamate autograft 16 months 85° 2 recurrent subluxation Durhan-Smith et al [ 25 ] Volar plate arthroplasty Minimum 6 months 95° 3 dorsal skin necrosis 1 pin track infection Hamer et al [ 26 ] Extension block splint 20.6 months 87° 3 treatment failure requiring surgery Newington et al [ 27 ] …”
Section: Authorsmentioning
confidence: 99%